Strategi Pembelajaran Inovatif dalam Pendidikan Inklusi di Tingkat Sekolah Dasar - Akramul Insan Zaer; M. Habibirrahim; Gusmaneli Gusmaneli (Edukasi Elita : Jurnal Inovasi Pendidikan, 2024)
Education as an Equal Right without Discrimination Education is considered a right that must be obtained by every individual regardless of background, economic status or physical condition. Within the framework of the national education system regulated by Law Number 20 of 2003, education is fully guaranteed without any form of discrimination. This encourages the importance of implementing inclusive education evenly at all elementary school levels. This article aims to outline creative learning strategies in the context of inclusive education, especially at the elementary school level, using a literature review as a basis. This research explores various library sources through search engines. The article explains that learning for students with special needs in elementary schools does not only focus on developing motor skills, but also on the ability to interact in a social environment. Teachers who implement creative learning strategies can increase the effectiveness of learning objectives, materials, media, teaching methods, evaluation, and student learning environments. Several learning strategies that can be applied to students with special needs in elementary schools include remedial teaching, deductive, inductive, heuristic, expository, classical, cooperative and behavior change strategies. To support this need, it is recommended that teachers explore the use of learning media that are friendly for students with special needs, such as puzzles, to create an inclusive learning environment and support optimal development for all students.